Practical applications in sports nutrition - Fink, Heather Hedrick; Burgoon, Lisa A.; Mikesky, Alan E. (Jones & Bartlett Learning, 2012)
"Practical Applications in Sports Nutrition, Third Edition provides students and practitioners with the latest sports nutrition information and dietary practices so they can assist athletes and fitness enthusiasts in achieving their personal performance goals. This text not only provides the most current sports nutrition guidelines and research but also includes the tools and guidance necessary to most appropriately"